Implementasi pendidikan anti-korupsi berbasis nilai-nilai pancasila - sholikhatul, hanifa (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze an effective implementation model for Anti-Corruption Education (ACE) by establishing Pancasila Values as its primary foundation. Corruption is viewed as a multi-dimensional problem that requires more than just legal action; it demands a deeper approach rooted in character building and moral awareness from an early age. The findings indicate that Pancasila operates through two core mechanisms: as a normative value system that establishes binding constitutional standards for transparent and accountable governance, and as a contextual value system that encourages the internalization of noble values like honesty and responsibility at the psychological and cultural level of society. The recommended implementation model is integrative and involves four key arenas: schools, universities (through Tridharma), society, and digital media. Successful implementation requires a synergy of structural (policy), cultural (local wisdom), and pedagogical (value-learning methods) dimensions, along with long-term commitment from all stakeholders.